2002
DOI: 10.2337/diabetes.51.2007.s358
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sensitivity of Pancreatic ATP-Sensitive Potassium Channels and Type 2 Diabetes

Abstract: Type 2 diabetes is generally perceived as a polygenic disorder, with disease development being influenced by both hereditary and environmental factors. However, despite intensive investigations, little progress has been made in identifying the genes that impart susceptibility to the common late-onset forms of the disease. E23K, a common single nucleotide polymorphism in K IR 6.2, the pore-forming subunit of pancreatic ␤-cell ATP-sensitive K ؉ (K ATP ) channels, significantly enhances the spontaneous open proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 64 publications
2
26
1
3
Order By: Relevance
“…1C). These results, together with the observation that sulfonylurea sensitivity is unaffected in the presence of the E23K polymorphism (23), suggest that the principal mechanism by which the E23K/I337V polymorphism alters LC-CoA sensitivity lies primarily within the Kir6.2 subunit.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…1C). These results, together with the observation that sulfonylurea sensitivity is unaffected in the presence of the E23K polymorphism (23), suggest that the principal mechanism by which the E23K/I337V polymorphism alters LC-CoA sensitivity lies primarily within the Kir6.2 subunit.…”
mentioning
confidence: 63%
“…The E23K and I337V mutations were introduced into the Kir6.2 gene using the protocol outlined in the QuikChange site-directed mutagenesis kit (Stratagene) and the generation of the mutations confirmed through sequence analysis. The ⌬C26Kir6.2 truncation mutant was constructed as previously described (23). Warner Instrument, Hamden, CT) to yield pipettes with a resistance of 2-6 M⍀.…”
Section: Methodsmentioning
confidence: 99%
“…The E23K variant is established as one of the few polymorphisms with a convincingly replicated impact on T2D susceptibility. In vitro 19 and in vivo 30 functional studies indicate that the K allele at E23K is associated with an increased open probability of the beta-cell K ATP channel and reduced insulin secretion. 19 In this respect, the strong clinical, phenotypic and epidemiological overlap between T2D and PCOS promotes a powerful argument for overlapping genetic influences.…”
Section: Discussionmentioning
confidence: 99%
“…Although results from initial studies are conflicting (45,46), large-scale association studies and meta-analyses have now identified the E23K polymorphism in KCNJ11 as a slight, but significant, risk factor in the complex development of type 2 diabetes (42,44,(47)(48)(49)(50). However, given the high allelic frequency of E23K in the general population (frequency of heterozygous EK genotype ϭ 47%; homozygous KK genotype ϭ 12%), the polymorphism is likely to represent a large population-attributable risk (41,48,51,52 (27,38,39,51,53) (see below). At the cellular level, an important question is: Just how much change in ATP sensitivity is necessary to cause significant impairment of insulin secretion?…”
Section: Part 1: 〉-Cell K Atp Channel and Diabetes: The Emerging Genementioning
confidence: 99%
“…Transgenic F1 mice from four of five founder lines expressing the truncated channels were severely hyperglycemic, and hypoinsulinemic, and died as neonates by day 5, most likely from acute ketoacidosis ( Fig. 2A) (51)(52)(53)(54). E23K is in linkage disequilibrium with another Kir6.2 polymorphism, I337V, which itself has no reported effect on channel activity (51,53).…”
Section: Part 1: 〉-Cell K Atp Channel and Diabetes: The Emerging Genementioning
confidence: 99%